Genomic analysis of Escherichia coli, Enterobacter hormaechei, and Cupriavidus gilardii isolated from Cacatua alba - Julia Penna de Andrade; Henrique da Silva Vieira; Camilla Faria Soares; Marcela Laryssa Oliveira Duarte; André Almeida Fernandes; Hannah Luiza Gonsalves Coelho; Victória Veiga Alves; Bertram Brenig; Vasco Ariston de Carvalho Azevedo; Flávia Figueira Aburjaile; Nelson Rodrigo da Silva Martins (Veterinary Research Communications, 2026)
The objective of this study was to perform genomic, phylogenomic, and phenotypic characterization of bacterial isolates from a captive Cacatua alba to investigate their antimicrobial resistance profiles, virulence-associated genes, and genomic relationships with publicly available strains. Bacterial isolates obtained from the lungs and encephalon were identified as Escherichia coli (AV037), Enterobacter hormaechei (AV038), and Cupriavidus gilardii (AV039). Comparative genomic analyses, phylogenomic reconstruction, and antimicrobial susceptibility testing (AST) were performed. Genomic analysis identified multiple antimicrobial resistance-associated genes in AV037, AV038, and AV039, with genes associated with efflux pumps, particularly those in the resistance-nodulation-cell division (RND) family, as the predominant resistance-associated mechanism identified. Most identified genes are intrinsic to the respective bacterial species and do not necessarily confer phenotypic antimicrobial resistance when present alone. Phenotypic testing confirmed multidrug-resistant (MDR) profiles, with resistance to β-lactams and aminoglycosides. Susceptibility to carbapenems was preserved in AV037 and AV038, whereas AV039 exhibited resistance to meropenem. Phylogenomic analysis demonstrated that AV037 and AV038 clustered with strains recovered from diverse hosts and geographic regions. In contrast, AV039 clustered predominantly with environmental and human-associated isolates, including strains harboring the mcr-5 gene. These findings are consistent with previous reports describing the recovery of C. gilardii from both environmental and clinical sources. Overall, this study documents the occurrence of MDR bacteria carrying resistance and virulence-associated determinants in a captive C. alba , highlighting the value of genomic surveillance to improve our understanding of the distribution of clinically relevant bacterial isolates across different ecological settings.